2016
DOI: 10.3892/etm.2016.3728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexpanthenol on acetic acid-induced colitis in rats

Abstract: While the pathogenesis of acetic acid (AA)-induced colitis is unclear, reactive oxygen species are considered to have a significant effect. The aim of the present study was to elucidate the therapeutic potential of dexpanthenol (Dxp) on the amelioration of colitis in rats. Group I (n=8; control group) was intrarectally administered 1 ml saline solution (0.9%); group II [n=8; AA] was administered 4% AA into the colon via the rectum as a single dose for three consecutive days; group III (n=8; AA + Dxp) was admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 42 publications
2
18
0
1
Order By: Relevance
“…There is some evidence for therapeutic potential of B5 in IBD, its supplementation showed anti‐oxidative, anti‐inflammatory and anti‐apoptotic effects leading to decreased tissue damage in a rat model for acute colitis. [ 67 ] Interestingly, dietary‐induced B5 deficiency in pigs induced spontaneous colitis that histologically resembled human UC. [ 68 ] Due to the direct link between B5 and CoA‐related SCFA production, increasing dietary B5 intake may enhance colonic SCFA levels and induce colitis recovery.…”
Section: Vitaminsmentioning
confidence: 99%
“…There is some evidence for therapeutic potential of B5 in IBD, its supplementation showed anti‐oxidative, anti‐inflammatory and anti‐apoptotic effects leading to decreased tissue damage in a rat model for acute colitis. [ 67 ] Interestingly, dietary‐induced B5 deficiency in pigs induced spontaneous colitis that histologically resembled human UC. [ 68 ] Due to the direct link between B5 and CoA‐related SCFA production, increasing dietary B5 intake may enhance colonic SCFA levels and induce colitis recovery.…”
Section: Vitaminsmentioning
confidence: 99%
“…Myloperoxidase is a hemoprotein enzyme abdudantly released from the neutrophils granules by inflammatory stimuli that catalyzes the formation of a number of reactive species (40). Studies have indicated that oxidative stress results from the shift of equilibrium between the prooxidant and anti-oxidant systems in favor of the pro-oxidant system which result of excessive production of free oxygen radicals and neutrophil infiltration (41,42). The study has also shown that administration of cinnarizine significantly reduce the expression of immunohistochemistry for markers of oxidative stress (myeloperoxidase and malondialdehyde) in colonic mucosa of experimentally induced colitis in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The slides were then washed with cold PBS and incubated with anti-rabbit secondary antibody (KeyGen). The histological examination was performed following the standard procedures described previously ( 19 ).…”
Section: Methodsmentioning
confidence: 99%